World Health Organization grade III meningiomas. A retrospective study for outcome and prognostic factors assessment. (3rd September 2015) - Champeaux, Charles; Wilson, Elena; Brandner, Sebastian; Shieff, Colin; Thorne, Lewis
Abstract : Background . Anaplastic meningiomas are uncommon primary intracranial tumours associated with high level of recurrence and low life expectancy. Through three institutions experience, we analysed the clinical characteristics of patients with malignant meningiomas to determine their outcome and identify prognostic factors that may influence recurrence and survival. Material and methods . A retrospective search identified 62 cases of WHO grade III meningiomas, of whom 9 (14.5%) were not considered in the survival analysis as no follow-up data were available. Thirty patients (48.4%) had a previous history of non-malignant meningioma surgery. The patients underwent a total of 139 surgical resections and 42 courses of radiotherapy of which 27 were given after the WHO grade III meningioma diagnosis. Results . Eighteen patients (29.5%) were re-operated for a relapse of their anaplastic meningioma. Median time between the first and the second surgery was 1.3 years. Median overall survival time was 3.5 years. Overall survival probabilities at 1, 2 and 5 years were 74.6%, 95% confidence interval (CI) [63.8, 87.1], 58.7%, 95% CI [46.4, 74.3] and 37.7%, 95% CI [25, 56.8], respectively. Extent of resection was associated with the survival. Discussion. This retrospective series highlights the poor prognosis associated with the diagnosis of malignant meningioma. Complete or subtotal resection may prolong the patients' survival. We could not confirm the usefulness of postoperative radiotherapy.